ALAT PENCACAH ECENG GONDOK UNTUK MENINGKATKAN PRODUKTIVITAS PAKAN ITIK KUR MEKAR ASIH - Pratama, Satria; Andrea, Ryan; Suwardi, Anwar; Priyatna, Rizal (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Citizen Business Group of Mekar Asih Panumbangan still uses conventional way to cut Eceng Gondok which is one of the components of duck woof mixture with using a knife. Therefore,they need a tool to cut the eceng gondok in order to be safe, effective and eficient. Eceng Gondok Cutting Machine which is named Apendok is made to increase the duck woof productivity of Citizen Business Group of Mekar Asih Panumbangan. The methodologies which were used in this project are identifying the problems and requirements,. The identification results was considered to design the eceng gondok cutting machine . Then, doing component manufacturing and assembly. After that, doing the trial and analysis and then deciding the conclusion. Apendok has been made with 1,2 kg/minutes or 72 kg/hour cutting capacity, 3/4 Hp power, 10 blades which is made of stainlesssteel. The advantages of Apendok are more effective, efficient, safety and has the big capacity, so that it could increase the duck woof productivity of Citizen Business Group of Mekar Asih Panumbangan.